2021
DOI: 10.1186/s13287-021-02171-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel live cell fluorescent probe for human-induced pluripotent stem cells highlights early reprogramming population

Abstract: Background Despite recent rapid progress in method development and biological understanding of induced pluripotent stem (iPS) cells, there has been a relative shortage of tools that monitor the early reprogramming process into human iPS cells. Methods We screened the in-house built fluorescent library compounds that specifically bind human iPS cells. After tertiary screening, the selected probe was analyzed for its ability to detect reprogramming c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…To date, only three studies have reported DPSC cultivation on microspheres in dynamic, three-dimensional shaking conditions [38,40,[60][61][62]. These three papers used dynamic conditions but were concerned only with cell differentiation and gene expressional changes and lacked any quantitative cell viability or cell proliferation data [40,61,62]. Cell expansion of DPSCs on microcarriers has been characterized in only two studies, using stationary and not dynamic conditions, as described above [38,60].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only three studies have reported DPSC cultivation on microspheres in dynamic, three-dimensional shaking conditions [38,40,[60][61][62]. These three papers used dynamic conditions but were concerned only with cell differentiation and gene expressional changes and lacked any quantitative cell viability or cell proliferation data [40,61,62]. Cell expansion of DPSCs on microcarriers has been characterized in only two studies, using stationary and not dynamic conditions, as described above [38,60].…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to resolve these pertinent issues surrounding both iPSCs and CRISPR/Cas9 technology are currently under active exploration. For example, highly precise surface-marker and fluorescence-based cell sorting approaches to yield pure populations of iPSCs and iPSC-derivatives have been reported by several groups (Lehnen et al 2017 ; Arias-Fuenzalida et al 2017 ; Schmitt et al 2017 ; Hoshina et al 2018 ; Patterson et al 2020 ; Sriram et al 2021 ). Several recent reports have also described promising approaches to improving the efficiency and reliability of the CRISPR/Cas9 system while minimizing the occurrences of unwanted off-target edits.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%